Bright Lights: Big Experiments! A public engagement activity for international year of light. (29th November 2016) - Downie, Jonathan; Morton, Jonathan A S; McCoustra, Martin R S
Abstract: The Bright Lights: Big Experiments! public engagement project enabled high school students Scottish S2 to prepare a short, 5 min video using their own words and in their own style to present a scientific experiment on the theme of light to their contemporaries via YouTube. This paper describes the various experiments that we chose to deliver and our experiences in delivering them to our partner schools. The results of pre- and post-activity surveys of both the pupils and teachers are presented in an effort to understand the impact of the project on the students, staff and their schools. The quality of the final video product is shown to be a key factor, increasing the pupils' likelihood of pursuing science courses and participating in further science engagement activities. Analysis of the evaluation methods used indicate the need for more sensitive tools to provide further insight into the impact of this type of engagement activity.